Aging and mixing as pseudo-chemical-reactions between, and on, particles: Perspectives on particle interaction and multi-modal ages in hillslopes and streams. (October 2019) - Benson, David A.; Schmidt, Michael J.; Bolster, Diogo; Harman, Ciaran; Engdahl, Nicholas B.
Abstract: The particle-tracking method was recently extended to allow inter-particle mass transfer and arbitrarily complex reactions by allowing each particle to represent any number of distinct chemical compounds. This methodology allows the tracking (and broadening due to mixing) of the age probability density function (PDF) on each particle. Aquifer heterogeneity leads to channeling and multi-modal age PDFs in stream samples. This observation supports the concept of age classes but clearly shows the more complicated interplay of dispersion, mixing, and travel times on the age distributions.